Development of Handbook for Handling Sports Injuries in Elementary School - Herli Esteria Br Ginting; Nurhayati Simatupang; Sabaruddin Yunis Bangun; Indra Kasih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to develop a textbook for primary school PJOK teachers in Tanah Karo, Berastagi district, a pocket book for handling sports injuries as a medium for handling injuries if they occur at school. This research is a research and development R&D (Research and Development). This research was carried out with 9 steps, namely: potential and problems, data collection, product design, design validation, use trials, product revisions, product tests, design revisions, and product revisions. In developing this pocket book, it has been validated by several experts, namely material experts, media experts, and linguists. This product trial was directly carried out by 10 actors, either small group trials or large group trials. The subject of this research is the teacher of elementary school PJOK in the sub-district of Berastagi, Karo district. The data collection technique used in this research is to use a questionnaire instrument. The data analysis technique of this research is descriptive qualitative and descriptive qualitative percentage. The results of this study indicate that a pocket book in providing an understanding of the management of sports injuries in elementary schools is feasible. The results obtained from material experts amounted to 77.5% or can be said to be feasible; media experts by 82.5% or appropriate; linguists 85% or worthy, and the results of the PJOK teacher's questionnaire in elementary schools regarding media, materials and also the language of pocket books showed that the assessment was categorized into 95.5%. The conclusion of this study is that the pocket book has been completed until it is introduced and understands about handling sports injuries in elementary schools in Berastagi District, Karo Regency.